Impacts of Artificial Soil Drought on Aboveground Biomass of Some Bangkok Street Tree Species: Comparisons Between Irrigated and Non-irrigated Potted Trees - Tor-ngern, Pantana (Asian Health, Science and Technology Reports, 2017)
Numerous research revealed that urban trees can play an important role in mitigation of rising atmospheric carbon dioxide in cities. To achieve sustainable urban greening management, selective tree planting is recommended, especially in an environment with projected intensified drought events. This study presents the assessment of changes in aboveground dry mass of potted trees of Pterocarpus indicus (Pi), Swietenia macrophylla (Sm) and Lagerstroemia speciosa (Ls), species commonly found in Bangkok, Thailand, under artificial soil drought during a one-week treatment. For each species, ten potted trees were used in the experiment: five trees were irrigated every day throughout the one-week period whereas the other five trees were withheld from water. Comparisons between the two tree groups in each species showed that soil drought induced leaf loss, resulting in significant reductions in transpirational surface (i.e., leaf area) and photosynthetic machinery (i.e., leaf mass) in all species, with the greatest decrease in Ls. The insignificant changes of woody dry mass under soil drought in these species indicated carbon allocation from leaf to root, with the greatest degree in Ls. Consequently, it may be implied that, for the same treatment period, Ls is the most sensitive to soil drought, exhibiting the greatest reduction in leaf area and leaf dry mass, and possibly increase in water absorbance capacity through enhanced root surface. Based on these findings, Pi and Sm may be recommended for planting in urban areas due to their slower responses and therefore higher tolerance to soil water deficit.